Analysis of the Blended Learning Model from the Perspective of Progressive Educational Philosophy - Noor Zinatul Hamidah; Muhammad Ghafar (Progressive Journal of Educational Science, 2025)
Technological advances in education have given birth to a new learning model called blended learning. The birth of blended learning aligns with the philosophical view of progressivism, which holds that education should continually adapt to the times. The problem is that every change offered by both progressivism and blended learning, while bringing various conveniences, also harms education. This study aims to analyze the blended learning model from a progressivist perspective, thereby clarifying the relationship between the two and assessing the suitability of both concepts for current Indonesian education. The research method is qualitative, with a literature review approach, drawing on various writings on blended learning and analyzing them through the theory of progressivism. This study concludes that the philosophies of progressivism and blended learning share similarities, namely in their orientation toward educational development and change. Blended learning is more about developing its learning model. At the same time, progressivism encompasses the development of all aspects of education, including methods, materials, curriculum, and objectives, in keeping with the changing times. Blended learning is a product of the philosophy of progressivism, which assumes that education must dynamically keep pace with the times. In contrast, blended learning is the education sector's response to these changes. Broadly speaking, blended learning, viewed from a progressive perspective, has many similarities across history, learning models, educators, and students. Both perspectives and histories emerge as innovations to conventional learning. Both share a student-centered learning model that focuses on the process rather than the material. Both concepts view the teacher as a monitor and facilitator, and view students as the center of learning.